2011
DOI: 10.1093/cercor/bhr037
|View full text |Cite
|
Sign up to set email alerts
|

Separating Intra-Modal and Across-Modal Training Effects in Visual Working Memory: An fMRI Investigation

Abstract: Working memory training is a useful tool to examine dissociations between specific working memory processes. Although current models propose a distinction between modality-specific working memory processes, to our knowledge no study has directly examined the effects of visual versus auditory working memory training. Functional magnetic resonance imaging was used to investigate whether visual working memory processes can be trained specifically and whether those effects can be separated from across-modal traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
91
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 53 publications
19
91
0
Order By: Relevance
“…As mentioned above short-term retention is necessary during novel word acquisition and should occur in modality-specific higher-order association cortices involved in language processing (Davis and Gaskell, 2009). The same higher-order visual association cortices were found to be recruited by verbal working memory (e.g., Ranganath et al 2004;Schneiders et al, 2011;Zimmer, 2008). Fiebach, Rissman, and D'Esposito (2006) for example demonstrated that during the retention period of a visual delayed cued recall task, pre-acquired (i.e., learned) words sustained greater activation in a language-sensitive left infero-temporal region relative to unlearned pseudo-words.…”
Section: Working Memory Training and Its Transfermentioning
confidence: 83%
See 3 more Smart Citations
“…As mentioned above short-term retention is necessary during novel word acquisition and should occur in modality-specific higher-order association cortices involved in language processing (Davis and Gaskell, 2009). The same higher-order visual association cortices were found to be recruited by verbal working memory (e.g., Ranganath et al 2004;Schneiders et al, 2011;Zimmer, 2008). Fiebach, Rissman, and D'Esposito (2006) for example demonstrated that during the retention period of a visual delayed cued recall task, pre-acquired (i.e., learned) words sustained greater activation in a language-sensitive left infero-temporal region relative to unlearned pseudo-words.…”
Section: Working Memory Training and Its Transfermentioning
confidence: 83%
“…A working memory task was applied in an additional run subsequently to the lexical run. The results have been described previously (Schneiders et al 2011). …”
Section: Fmri Sessionsmentioning
confidence: 95%
See 2 more Smart Citations
“…In recent years, many studies have found that the training of working memory has a significant effect on the brain's nervous system, the main manifestations are enhanced, attenuated, or rearrangement of nervous system activation [5,6].…”
Section: Introductionmentioning
confidence: 99%